Popular Mobilization and human security In Local Society - محمد حميد علوان Mohammed Hamed Alwan (College of Education for Women, 2018)
The definition of the role of any institution in society is achieved through its objectives, The same is true for the military and how to deal with security threats in the humanitarian field ,Terrorism, which has almost replaced the traditional pattern of war, has waged a street war and intimidated individuals, families and society ,On the other hand, he found someone to meet him from a popular crowd of volunteers to defend their homeland from different sects, sects and religions,  Thus, our study will be exposed to the role of popular mobilization in human security from a sociological point of view in Samarra, a field study of 100 male and female respondents.